STUDI FENOMENOLOGI PENGALAMAN LANSIA DENGAN DEMENSIA MENGIKUTI CST (COGNITIVE STIMULATION THERAPY) DI LKS-LU PANGESTI LAWANG - Berliany Venny Sipollo (Jurnal Keperawatan Malang, 2022)
Background: Dementia affects each older adults in different ways depending on the impact of the disease and the personality of the older adults before falling ill. Objective: This qualitative study aims to explore the experience of the older adults following Cognitive Stimulation Therapy at LKS-LU Pangesti Lawang. Methods: Data collection techniques in the study used in-depth interviews using semi-structured interview guidelines. The number of samples was 27 older adults who received Cognitive Stimulation Therapy (CST) three times per week for 5 weeks. Results: The results of interviews with the older adults after participating in Cognitive Stimulation Therapy (CST) obtained 5 themes as follows: 1. Increased memory; 2. Discussion together; 3. Happy; 4. Communication improves; 5. Increase enthusiasm and motivation. Conclusion: Cognitive Stimulation Therapy improves memory in the demented older adults. Nurses and health care teams can apply cognitive stimulation therapy regularly to the older adults. Keywords: Dementia, Older Adult, Cognitive Stimulation Therapy.